ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY DAN KETERLAMBATAN PUBLIKASI LAPORAN KEUANGAN PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA - NOVITASARI, MAYA (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2018)
This study aims to analyze and find empirical evidence of factors that affect audit delay and delayed publication of financial statements on consumer goods companies listed on the stock exchange Indonesia in 2012-2015. Factors studied in this research are liquidity, profitability, the size of a public accounting firm and auditor opinion as independent variable while audit delay and delayed publication of financial statements as dependent variable. The sample consists of 21 companies listed in Indonesia Stock Exchange selected by using purposive sampling. The analytical tool used is multiple regression analysis to measure audit delay, logistic regression to measure the delay of publication of financial statements and spearman correlation to measure the relationship between audit delay and delayed publication of financial statements. Partial hypothesis test results show that liquidity, profitability, auditor opinion no significant effect on audit delay and publication delay while the size of a public accounting firm there is a significant influence on audit delay and the delay of publication. The correlation result indicates that audit delay has no significant effect on the delay of publication